The regulation of DNA synthesis in quiescent lymphocytes by cytoplasmic inhibitors. - Gutowski, J K (1985)
We previously have shown that proliferating lymphoid cells contain an extractable cytoplasmic protein that is capable of inducing DNA synthesis in isolated quiescent nuclei (activator of DNA replication, ADR). ADR is present in continuously proliferating (transformed) lymphoblastoid cell lines and in mitogen- or interleukin 2-stimulated human peripheral blood leukocytes (PBL) but is not detectable in extracts from resting (unstimulated) PBL. In the present study, we investigated the possibility that quiescent PBL may contain a factor than can inhibit ADR activity. We found that unstimulated human PBL contain a heat-stable protein greater than or equal to 50,000 Da that is capable of suppressing the induction of DNA synthesis in isolated nuclei by ADR derived from both normal and neoplastic sources. The inhibitor was not detectable in freshly isolated PBL but appeared within the cells after a brief (2-6 hr) culture period. Depletion experiments revealed that the inhibitor was neither derived from nor dependent upon the macrophage component of the PBL cultures. These results suggest that one mechanism by which resting lymphocytes may maintain quiescence may involve the suppression of cytoplasmic mitogenic signals by intracellular inhibitors. In addition, the implications of our findings provide a possible explanation for the loss of growth control in abnormal proliferative states, such as neoplasia.